Conversões e negociações: um estudo dos relatos de missionários protestantes da Church Missionary Society em Uganda-África (1876-1890) - Damasceno, Yuri Wicher [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Trabalhamos a partir do conceito de representações utilizados pela “Nova” História Política que foi utilizado na compreensão dos relatos de missionários protestantes da Church Missionary Society liderados por Alexander Mackay, que atuaram na região central da África durante o final do século XIX (1876-1890), engajados em um projeto evangelizador para angariação de novos convertidos, principalmente a partir da análise da fonte primária The Wonderful History of Uganda publicado por Joseph Dennis Mullins em 1904 após a reunião de uma série de relatos produzidos no período utilizado como recorte temporal. O trabalho visa reconhecer e explanar a voz dos africanos suas atuações enquanto resistentes e negociadores do processo que levou à incursão da religião cristã protestante no território do antigo reino de Buganda.

We work from the concept of representations used by the “New” Political History that was used in the understanding of Protestant missionaries of the Church Missionary Society reports led by Alexander Mackay, who worked in Central Africa during the late nineteenth century (1876-1890 ), engaged in an evangelizing project for attracting new converts, particularly from the analysis of the primary source the Wonderful History of Uganda published by Joseph Dennis Mullins in 1904 after meeting a series of reports produced in the period used as a time frame. The work aims to recognize and explain the voice of Africans his performances as tough negotiators and the process that led to the incursion of Protestant Christian religion in the territory of the ancient kingdom of Buganda.
Conversions and Negociations: a study of protestant missionaries from Church Missionary Society in Uganda-Africa (1876–1890)
Keywords: Missionários; África; Protestantismo; Protestantism; Missionaries; Uganda